Anti-Müllerian Hormone Regulation of Synaptic Transmission in the Hippocampus Requires MAPK Signaling and Kv4.2 Potassium Channel Activity - Wang, Kang; Xu, Fuhua; Maylie, James; Xu, Jing (Frontiers in Neuroscience, 2021)
Anti-Müllerian hormone (Amh) is a paracrine factor generated peripherally by the gonads to regulate gonadal function in adult mammals. We recently reported that Amh and Amh-specific receptor (Amhr2) are expressed in the hippocampus, and exogenous Amh protein rapidly increased synaptic transmission and long-term synaptic plasticity at the CA3-CA1 synapses. Here we examined the cell-specific expression of Amhr2 and the cellular mechanism of rapid boosting effect of Amh on synaptic transmission in mouse hippocampus. Immunofluorescence staining showed that Amhr2 was specifically expressed in the soma and dendrites of hippocampal pyramidal neurons, but not glial cells. Electrophysiological recordings on acute hippocampal slices showed that Amh did not affect AMPAR-mediated or NMDAR-mediated excitatory postsynaptic currents at the CA3-CA1 synapses. The small-conductance Ca2+-activated K+ channel (SK2) and A-type K+ channel (Kv4.2) contribute to shaping excitatory postsynaptic potentials (EPSPs) at the CA3-CA1 synapses. Bath application of apamin to block SK2 did not alter Amh effect on increasing EPSPs, whereas blocking Kv4.2 channel with 4-aminopyridine, or chelating internal Ca2+ with BAPTA occluded the action of Amh on boosting EPSPs. Kv4.2 activity is regulated by p38 mitogen-activated kinase (MAPK). Blocking p38 MAPK with SB203580 occluded the effect of Amh on increasing EPSPs. These results show that Kv4.2 channel contributes to the rapid action of Amh on boosting synaptic transmission in a Ca2+- and p38 MAPK-dependent manner. Our findings provide functional evidence that Amh enhances synaptic transmission through Kv4.2 channel in the hippocampus, suggesting a possible role of Kv4.2 channel in Amh-regulated neuronal process underlying learning and memory.